Effectiveness and perception of augmented reality in the teaching of structured programming fundamentals in university students - Oyarvide, Wellington Remigio Villota; Salvatierra, Shirley Betty Reyes; Saltos, Guillermo Del Campo (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Even while studying programming languages is essential for science and technology education, some students, especially novices, may find it challenging. One reason might be that these pupils are unable to comprehend programming basics, notably the usage of selective and repeated structures (loops), which are too complex and abstract for them to comprehend. OBJECTIVES: Programming structured applications requires understanding the relationship between variable-operators and declarations, so a more intuitive and practical visualization technique is needed. In view of this, this article presents an augmented reality (AR) learning system using a DF-RA mobile application that offers visual representation and interactivity to help college students in entry-level computer science-related majors learn to program structured applications using dynamic and interactive flowcharts. METHODS: In order to examine the influences of said Augmented Reality-enhanced system on student learning, an experiment will be carried out within the group with 34 university students. All students used both an augmented reality-enhanced version and a conventional paper version (classic methodology with paper flowcharts). RESULTS: The expected results is that the augmented reality version through the DF-RA mobile application made students have a better learning efficiency than the traditional paper system. In addition, the system enhanced with Augmented Reality also made students have improved perceptions in terms of system usability, flow experience, and usage perception. CONCLUSION: Experimental findings were analyzed to demonstrate that the augmented reality learning system increases students’ motivation to study structured programming fundamentals and their practical competence.